Environmental Spending: The Portal to a Sustainable, Green Economic Approach. Les Dépenses environmentales: Le portail d'une approche économique durable et verte - BOUZIDA, SAOUSSEN; CHAOUI, CHAFIA (Finance and Business Economies Review, 2019)
Even though environmental problems are not new, we have only recently begun to understand their dimensions after observing the impact of environmental degradation on weakening economic development and decreasing its potential, and the main solution is “Environmental spending”. In order to that, this paper will present the different aspects of Green Economics on Environmental Spending as well as the successful OECD strategy as a guideline for future Algerian investments in the green field. Our main findings were that Algeria has paid some attention to the environment; however its efforts were not enough and should be supported through some privet environmental investments. To conduct this paper, we used the descriptive &analytical approach, data has been collected from multiple sources which helped us to analyze the ideas, and connect them logically and scientifically.